Features of Formation of Ohmic Contacts and Gate on Epitaxial Heterostructure of AlGaN / GaN High Electron Mobility Transistor - I.A. Rogachev; A.V. Knyazkov; O.I. Meshkov; A.S. Kurochka (Журнал нано- та електронної фізики)
Reported about study of processes of formation of Ti / Al / Ni / Au ohmic contacts to heterostructures AlGaN / GaN and gate Ni / Au. Investigated of process recess the semiconductor layer for minimum resistance of ohmic contact – 0.4 Ohm·mm. Studied influence of encapsulation ohmic contacts on their surface morphology.